The slow lane: A study on the diffusion of full-electric cars in Italy - Monica Bonacina; Mert Demir; Antonio Sileo; Angela Zanoni (Fondazione Eni Enrico Mattei (FEEM), 2024)
The transition to a zero-emission car fleet is a pivotal element of Europe's decarbonisation strategy. Italy's participation in this trajectory is significant, given the size of its car fleet. Currently, only battery electric (BEVs) and hydrogen-powered are considered zero-emission vehicles. The final update of the National Energy and Climate Plan (NECP) includes an ambitious target for the diffusion of electric cars in the Italian fleet. The aim is to have a total of 4.3 million electric cars on the roads by 2030. However, by the end of 2023, the Italian e-fleet totalled 220,000 cars, which equals a mere 0.5% of the overall car population and 5% of the target. The objective of this study is threefold: firstly, to estimate the likely diffusion of electric cars in the Italian market; secondly, to assess the prospects for their penetration in the fleet in the coming years; and thirdly, to evaluate the consistency of the current diffusion path with the NECP target. Diffusion paths are derived using Bass and logistic diffusion models. We consider a business-as-usual scenario based solely on historical trends, and an accelerated diffusion alternative scenario, in which we assume that by 2023 new BEV models will enter the Italian car market, raising the market potential for this powertrain to the same level as the most successful non-plug-in hybrid models. Both scenarios show that, in the absence of further significant shifts, the deployment paths will be totally insufficient to meet NECP 2030 target. Fewer than half a million consumers appear to be interested in buying one of the battery electric models currently on sale in the business-as-usual scenario. The low share of enthusiastic potential adopters of BEVs, the increasing useful life of passenger cars, the lack of highly successful BEV models, the limited impact of the incentive schemes until 2023 and the strong competition from other alternative technologies (besides non-plug-in hybrids and LPG) continue to impede the penetration of electric powertrains in the Italian fleet. Incentive schemes and decarbonisation strategies must undergo major revision to achieve a path consistent with net-zero emission goals.
Keywords: N74; Q55; Q58; R40; 330; sustainable mobility; road transport decarbonization; electric vehicle adoption; automotive market; Italian National Energy and Climate Plan (NECP)